A novel surface-oxidized rigid carbon foam with hierarchical macro-nanoporous structure for efficient removal of malachite green and lead ion. (20th March 2022) - Zhang, Qiyun; Wu, Renquan; Zhou, Yunhong; Lin, Qilang; Fang, Changqing
Highlights: Oxidized rigid carbon foam (ORCF) with high porosity and open cell is prepared. The ORCF possesses a fluffy and porous surface with rich O-containing groups. The ORCF has a hierarchical macro-nanoporous structure with mesoporous nature. High adsorption capacities and partition coefficients for MG and Pb 2+ are achieved. The ORCF is an efficient adsorbent with good cycling stability for MG and Pb 2+ . Abstract: This study developed a method to fabricate a surface-oxidized rigid carbon foam (ORCF) with hierarchical macro-nanoporous structure via KOH activation of the carbon foam with two kinds of macropores followed by HNO3 hydrothermal oxidation. The structures of the prepared ORCF were characterized using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier transform infrared (FTIR) spectra, X-ray photoelectron spectroscopy, and N2 adsorption-desorption analyzer. Results demonstrate that the ORCF possesses a fluffy and porous structure with rich oxygen-containing groups. There are numerous through-holes on its pore surfaces connected with two-level macropores forming hierarchical macroporous channels. Meanwhile, the ORCF remains a good bulk structure with a compression strength of 0.74 MPa at a bulk density of 0.09 g cm −3 . Batch adsorption experiments for malachite green (MG) and Pb 2+ were studied through the single variable method to investigate the effects of different initial conditions on its adsorption process. The ORCF has maximum adsorption capacities for MG and Pb 2+ of 587.68 mg g −1 and 157.80 mg g −1 with high partition coefficients of 17.41 mg g −1 µM −1 and 14.86 mg g −1 µM −1, respectively. The experimental data are suitable for Langmuir isotherm and Pseudo-second-order kinetic models, which correspond to monolayer chemisorption. Thermodynamic analysis indicates that the adsorption process is spontaneous and endothermic. Moreover, the removal percentages of MG and Pb 2+ by the ORCF could remain above 90% after five cycles, implying that the ORCF is an efficient adsorbent with good adsorption ability and cycling stability. Graphical abstract: Image, graphical abstract